PENGELOLAAN BIMBINGAN KONSELING DI SEKOLAH MENENGAH PERTAMA - Rita Lisnawaty (UNIVERSITAS BENGKULU, 2016)
The objective of this research was to compare the differences and similiraties of the management of counceling service between public junior high school number 2 and number 4 inBengkulu city. The research used comparative method. The subjects of this study were the teachers of counceling service and students. The techniques of collecting data were interview,observation and documentation. The results show that the differences include objectives fasilities, schedule. The similiraties include both schools have program organization structur, significances for students. Thus the counceling service management at public junior high school number 2 andnumber 4 Bengkulu in city has differences and similiraties in the planning, implementation, monitoring and evaluation programs.Keywords: management, counceling service.